How to teach modern languages-- and survive! - Pleuger, Jan, 1942- (Modern languages in practice, 2001)
This book sets out some of the practical techniques Jan Pleuger has used with children of all ages and abilities, and most of the ideas can also be applied to adult learners. These practical strategies are aimed at reducing both pupil and teacher anxiety and provides a deep understanding of the psychological dynamics of the modern language classroom. The result is an enjoyable book, entertainingly written and bursting with tips for busy Modern Language teachers.